Molahidatidosa from Pathophysiology to Clinical: Literature Review - Rachmat Hidayat; Irawan Sastradinata (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Hydatidiform is a gestational trophoblast disease which is histopathologically characterized by the proliferation of avascular trophoblast cells and corial villi and undergoing hydrophic degeneration. The proliferation of trophoblast cells in hydatidiform moles can be in the form of cytotrophoblast, syncytiotrophoblast or intermediate trophoblast proliferation.